Androgen deprivation therapy plus apalutamide as neoadjuvant therapy prior radical prostatectomy for patients with unresectable prostate cancer - Wei, Yongbao; Zhang, Ruochen; Zhong, Dewen; Chen, Zhensheng; Chen, Gen; Yang, Minggen; Lin, Le; Li, Tao; Ye, Liefu; Chen, Lili; Zhu, Qingguo (Frontiers in Pharmacology, 2023)
Whether neoadjuvant therapy confers a survival benefit in advanced prostate cancer (PCa) remains uncertain. The primary endpoints of previous retrospective and phase II clinical studies that used neoadjuvant therapy, including androgen deprivation therapy combined with new-generation androgen receptor signaling inhibitors or chemotherapy, were pathological downstaging, progression-free survival, prostate-specific antigen relief, and local symptom improvement. To the best of our knowledge, no studies have explored the efficacy and safety of neoadjuvant therapy in improving the surgical resection rate in cases of unresectable primary tumors of PCa. We first designed this retrospective study to evaluate the potential value of apalutamide as neoadjuvant therapy in improving the resectability rate of radical prostatectomy (RP). We initially reported 7 patients with unresectable primary lesions who underwent neoadjuvant apalutamide treatment for a median of 4 months, and all of them successfully underwent RP treatment. Our study supported apalutamide as neoadjuvant therapy, which helped improve RP's success rate and did not significantly increase perioperative complications, and the neoadjuvant therapy was controllable. Our findings' clinical value and benefit for survival still need further clinical research to confirm.